2012
DOI: 10.1042/cs20110432
|View full text |Cite
|
Sign up to set email alerts
|

A novel vasculo-angiogenic effect of cilostazol mediated by cross-talk between multiple signalling pathways including the ERK/p38 MAPK signalling transduction cascade

Abstract: Cilostazol is an anti-platelet agent with vasodilatory activity that acts by increasing intracellular concentrations of cAMP. Recent reports have suggested that cilostazol may promote angiogenesis. In the present study, we have investigated the effect of cilostazol in promoting angiogenesis and vasculogenesis in a hindlimb ischaemia model and have also examined its potential mechanism of action in vitro and in vivo. We found that cilostazol treatment significantly increased colony formation by human early EPCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 53 publications
3
64
1
Order By: Relevance
“…In line with this, Wang et al also demonstrated a decrease of VEGF expression by cilostazol in streptozotocin-induced diabetic inflammation [40]. In contrast, several recent studies could show a stimulation of VEGF expression upon cilostazol treatment, including conditions of hind limb ischemia [41,42] and transient forebrain ischemia [43]. The latter results are in line with the results of the present study, indicating an increased VEGF expression in livers of cilostazol-treated, hepatectomized animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with this, Wang et al also demonstrated a decrease of VEGF expression by cilostazol in streptozotocin-induced diabetic inflammation [40]. In contrast, several recent studies could show a stimulation of VEGF expression upon cilostazol treatment, including conditions of hind limb ischemia [41,42] and transient forebrain ischemia [43]. The latter results are in line with the results of the present study, indicating an increased VEGF expression in livers of cilostazol-treated, hepatectomized animals.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, several reports are published, demonstrating that a cilostazolinduced increase of VEGF expression is associated with an increased vascularization [41][42][43]. Surprisingly, our data indicate a reduction of tumor vessel density (density of PECAM-1-positive cells) after cilostazol treatment, despite an increased VEGF expression.…”
Section: Discussioncontrasting
confidence: 44%
“…It is indicated for peripheral artery disease-related intermittent claudication. 3,8 Interestingly, the compound has been reported to have a number of additional effects, including protecting endothelial cells from apoptosis, 9 preventing monocyte adhesion to endothelial cells, 10,11 stimulating the release of angiogenic factors, 12 and activating endothelial NO synthase …”
mentioning
confidence: 99%
“…[1][2][3] Diabetes mellitus is a significant risk factor for the development of atherosclerotic diseases and an increase in cardiovascular mortality. 4 Hyperglycemia decreases nitric oxide (NO) production, 5 and reduces vasculoangiogenesis with resultant impaired function of endothelial progenitor cells (EPCs) and less flow recovery after hind limb ischemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation